Maternal Knowledge about Stunting and Malnutrition in Children Under Five Years Old at Puskesmas Candi Sidoarjo - Maura, Fidela; Rahariyani, Loetfia Dwi; Wulan Dari, Tanty (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2024)
Toddlerhood is an important period in the process of human growth and development. Malnutrition and stunting in toddlers can be influenced by various factors. The purpose of this study was to determine the level of maternal knowledge about stunting and malnutrition in children under five. Research Methods: This study used a correlation study method using a cross sectional approach involving 45 respondents of mothers of toddlers at Candi Sidoarjo Health Center selected through consecutive sampling technique. Data collection was carried out using a knowledge questionnaire sheet about stunting and malnutrition. The results showed that the majority of mothers' knowledge about stunting had less knowledge, as many as 17 people (38%). The majority of mothers' knowledge about malnutrition had less knowledge, as many as 25 people (56%). Seeing the results of this study, it is hoped that mothers of toddlers understand more about the importance of nutritional intake in toddlers so as not to get stunted or malnutrition.